Time of Emergence of Climate Signals over Vietnam Detected from the CORDEX-SEA Experiments - Nguyen-Thuy, Huong (Archīum Ateneo, 2020)
This study uses six regional climate model (RCM) experiments from the Coordinated Regional Climate Downscaling Experiment—Southeast Asia (CORDEX-SEA) and their driving global climate models (GCM) to investigate the model performance and the time of emergence (ToE) of temperature and precipitation over Vietnam and its seven sub-climatic regions. A simple delta (multiplicative) bias correction (BC) method has been applied to the model temperature (precipitation). Results show clear added values of the BC downscaled products compared to their driving GCMs, particularly for temperature. The projected trends of RCM temperature during 2006–2100 under two representative concentration pathway (RCP) RCP4.5 and RCP8.5 scenarios are similar to those of their driving GCMs. Consequently, the RCM-based ToE and GCM-based ToE are generally consistent for temperature, occurring in the beginning of the 21st century. The earliest and latest ToE occur in summer and winter, respectively. The seasonal differentiation for temperature-ToEs is stronger in the northern areas compared to the southern areas of Vietnam. The ToE difference between two RCPs increases from the south to the north. As for precipitation, ToE occurs quite late, in the latter half of the 21st century at the earliest. Results from ToE estimations also indicate an opposite precipitation trend between the GCMs and RCMs. The largest difference is in summer over the southern region of Vietnam. The opposite trend between the GCM and RCM precipitation under a similar increasing temperature implies the uncertainty in assessing the impact of warming on hydrological cycles in Vietnam.